Thematic Unity Theory in the Qur'an: Comparative Analysis between Tafsir Al-Farahi and Tafsir Sa'id Hawwa - Zihan Amalia Shabrina; Andri Nirwana. AN (al-Afkar, Journal For Islamic Studies, 2026)
This study analyzes the concept of thematic unity (al-wahdah al-mawdhu‘iyyah or nazm) in Qur’anic exegesis as developed by two important figures in modern exegesis, Hamiduddin Al-Farahi (1863–1930) and Sa‘id Hawwa (1935–1989) (Khanan et al., 2025). Both represent two distinct but complementary methodological styles: Al-Farahi with a structural-linguistic approach that emphasizes the internal coherence of the text through the concepts of ‘umud (the central theme of the surah) and nazm (verse coherence), while Sa‘id Hawwa developed a thematic-conceptual exegesis (tafsir mawdhu‘i) that highlights the inter-verse relationships (munasabah) and the moral and social relevance of revelation. Using qualitative-comparative methods and a hermeneutical approach to interpretation, this study explores the epistemological similarities and methodological differences between the two, and assesses their implications for modern exegesis studies. The results demonstrate that the thematic unity theory offers a new paradigm for understanding the Quran integratively rejecting atomistic readings and emphasizing that each chapter possesses an interconnected architecture of meaning. The synergy between the nazm (Farahi) and the thematic-applicative (Hawwa) approaches enriches exegesis studies with a balance between scientific rigor and contextual relevance (Basir et al., 2022). These findings are expected to contribute to the development of a modern exegesis methodology that is not only academic and linguistic, but also reflective of the social realities of contemporary Muslims.